Antisense-Mediated RNA Targeting: Versatile and Expedient Genetic Manipulation in the Brain - Zalachoras, Ioannis; Evers, Melvin M.; van Roon-Mom, Willeke M.; Aartsma-Rus, Annemieke M.; Meijer, Onno C. (Frontiers in Molecular Neuroscience, 2011)
A limiting factor in brain research still is the difficulty to evaluate in vivo the role of the increasing number of proteins implicated in neuronal processes. We discuss here the potential of antisense-mediated RNA targeting approaches. We mainly focus on those that manipulate splicing (exon skipping and exon inclusion), but will also briefly discuss mRNA targeting. Classic knockdown of expression by mRNA targeting is only one possible application of antisense oligonucleotides (AON) in the control of gene function. Exon skipping and inclusion are based on the interference of AONs with splicing of pre-mRNAs. These are powerful, specific and particularly versatile techniques, which can be used to circumvent pathogenic mutations, shift splice variant expression, knock down proteins, or to create molecular models using in-frame deletions. Pre-mRNA targeting is currently used both as a research tool, e.g. in models for motor neuron disease, and in clinical trials for Duchenne muscular dystrophy and amyotrophic lateral sclerosis. AONs are particularly promising in relation to brain research, as the modified AONs are taken up extremely fast in neurons and glial cells with a long residence, and without the need for viral vectors or other delivery tools, once inside the blood brain barrier. In this review we cover 1. The principles of antisense-mediated techniques, chemistry and efficacy. 2. The pros and cons of AON approaches in the brain compared to other techniques of interfering with gene function, such as transgenesis and short hairpin RNAs, in terms of specificity of the manipulation, spatial and temporal control over gene expression, toxicity and delivery issues. 3. The potential applications for Neuroscience. We conclude that there is good evidence from animal studies that the CNS can be successfully targeted, but the potential of the diverse AON-based approaches appears to be under-recognized.